Matharpacady-02.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Matharpacady has a network of lanes and alleys where children play games and have fun with neighborhood cats. The idyllic setting of the gaothan, away from the din and chaos of the city outside, is reminiscent of susegad, typical of the Goan culture. Derived from the Portuguese sossegado (meaning 'quiet'), it is used to describe the relaxed, laid-back attitude towards life that defined the lifestyle in the former Portuguese territory.